Promotion Mix Dan Kualitas Pelayanan Pengaruhnya Terhadap Keputusan Pembelian Dengan Kepuasan Konsumen Sebagai Variabel Intervening - Herlina Gonam; Uju Suji'ah (Universitas Muhammadiyah Pontianak, 2026)
This study determines the influence of promotion mix and service quality on purchasing decisions with consumer satisfaction as an intervening variable among Morgan's Kebab consumers in Yogyakarta City. The sample comprised 100 respondents selected through purposive sampling, analyzed using SEM-PLS with SmartPLS 4.0.9.9. The results show that promotion mix has a positive and significant effect on purchasing decisions and consumer satisfaction; service quality has no significant direct effect on purchasing decisions but significantly affects consumer satisfaction; and consumer satisfaction significantly affects purchasing decisions and mediates the effects of promotion mix and service quality on purchasing decisions. Keywords: Promotion Mix; Service Quality; Purchasing Decisions; Consumer Satisfaction